The Green Solow model with natural resources constraint: A theoretical note - Reyes, Rachel C. (Animo Repository, 2011)
This note extends Brock and Taylor's (2010) Green Solow model to consider natural resources constraint by adopting a specific Cobb-Douglas production function. The augmented model demonstrates simultaneously how the limit of the natural resources and emissions abatement activities figure in determining the level of steady state capital per effective worker and exploring the dynamics of vital macroeconomic variables such as output growth and emissions growth, together with their corresponding per worker values. With the society's desire for output to expand and carbon emissions to diminish, this model highlights the importance of improving emissions abatement technology in attaining these goals. Additionally, it presents the impact of natural resource depletion on emissions along the balanced growth path. © 2011 De La Salle University, Philippines.